E-031 Conservative management for an incidentally found pial arteriovenous fistula in an elderly patient. (23rd July 2022) - Chang, D; Babadjouni, R; Eboli, P
Abstract : Introduction: Pial arteriovenous fistulas (pAVFs) are rare vascular malformations requiring intervention in neonates and infants, but the natural course in the elderly population remains unclear. Methods: The authors describe the case of a 78-year-old male with transient symptoms of vertigo and diplopia. Workup including magnetic resonance imaging (MRI) and computed tomography angiography (CTA) demonstrated no acute infarct or hemorrhage to explain the symptoms, but a vascular lesion was noted in the right cerebellum. Digital subtraction angiography confirmed the diagnosis of a right cerebellar pAVF, filling mainly from distal superior cerebellar artery branches, draining directly into dilated cortical veins with no obvious AVM nidus. After review of the literature and discussion with the patient, conservative monitoring with serial imaging was elected. Results: The patient was followed up with delayed CTA which demonstrated stable findings, and the patient continued to do well, remaining neurologically asymptomatic. pAVFs are often symptomatic lesions when found in neonates and infants, necessitating intervention. The findings of these lesions in the elderly (>70 years of age) are exceedingly rare in the literature and may follow a benign natural course. Conclusion: Without direct evidence of associated symptoms or pathologic findings, conservative management with serial imaging may be a reasonable option for pAVFs. Disclosures: D. Chang: None. R. Babadjouni: None. P. Eboli: None.